Degradação da tetraciclina em efluentes de carcinicultura por eletro-oxidação - Andrade, Ana Karolyne Fontes (2025)
The increasing occurrence of antibiotics in aquaculture effluents represents an environmental and public health challenge, mainly due to the induction of microbial resistance. Among these compounds, tetracycline stands out for its frequent use in shrimp farming. This study evaluated electrochemical oxidation as an advanced process for tetracycline degradation in shrimp-pond effluents, employing a filter-press reactor operated in closed recirculation with a metal-oxidebased anode (Ti/RuO₂–Sb₂O₄–TiO₂). Operational variable optimization (current density, time, and flow rate) was performed using a Central Composite Rotational Design (CCRD). Under optimal conditions (60 mA cm⁻², 3 h, 4 L min⁻¹), complete degradation was achieved in the real effluent within 10 min, with up to 99.42 % removal in the synthetic effluent. The energy consumption ranged from 6.7 to 16.8 Wh L⁻¹, resulting in an estimated cost of R$ 4.46–11.19 m⁻³ (at R$ 0.666 kW h⁻¹), which is competitive compared to systems using aluminum or iron electrodes. The physicochemical characterization of the effluent indicated pH values between 7.76 and 8.12, conductivity of 24 mS cm⁻¹, total nitrogen of 10.2 mg L⁻¹, and phosphate of 0.22 mg L⁻¹—the latter above the reference value for eutrophication prevention, yet close to the limits established by Brazilian Resolution CONAMA No. 430/2011. The electro-oxidation process led to a 32 % decrease in COD and an increase in BOD, evidencing partial oxidation of organic matter and the formation of more biodegradable intermediates. These findings demonstrate the potential of the electrochemical system as a pre-treatment stage, allowing integration with subsequent biological processes to enhance organic mineralization, nutrient removal, and overall environmental compliance. Electrochemical oxidation proved to be a promising, efficient, and environmentally safe alternative for the treatment of antibioticcontaminated aquaculture effluents, directly contributing to the United Nations Sustainable Development Goals (SDGs), particularly SDG 6 (Clean Water and Sanitation), SDG 3 (Good Health and Well-Being), and SDG 14 (Life Below Water).